2011
DOI: 10.1016/s0034-7094(11)70045-9
|View full text |Cite
|
Sign up to set email alerts
|

Pain and the Protagonism of Women in Parturition

Abstract: In this context, pain represented one of the main building blocks of female social representations on parturition, contributing to the ascending curve of cesarean section indices in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 7 publications
0
14
0
7
Order By: Relevance
“…However, some studies on post-natal sexuality have found no significant difference between women who had vaginal births and those who had surgicalcesarean deliveries (Klein et al, 2009;Belentani et al, 2011). Another fear of women is that of not being able to handle the pain associated with vaginal birth; a number of studies describe these fears and their associations with the images and stories that circulate in Brazil about vaginal birth in a family context, and in images divulged by the media, among others (Rodrigues and Siqueira, 2008;Pereira et al, 2011;Pinheiro and Lobo, 2012;Tostes and Seidl, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies on post-natal sexuality have found no significant difference between women who had vaginal births and those who had surgicalcesarean deliveries (Klein et al, 2009;Belentani et al, 2011). Another fear of women is that of not being able to handle the pain associated with vaginal birth; a number of studies describe these fears and their associations with the images and stories that circulate in Brazil about vaginal birth in a family context, and in images divulged by the media, among others (Rodrigues and Siqueira, 2008;Pereira et al, 2011;Pinheiro and Lobo, 2012;Tostes and Seidl, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptores: Parto Normal; Trabajo de Parto; Parto Domiciliario; Parto Humanizado; Enfermería Obstétrica. 1,2,4,5,6 Students, undergraduate degree in nursing from the University Center Anhanguera in Niterói, Rio de Janeiro (RJ), Brazil. Email: alane_sc@hotmail.com ORCID iD: http://orcid.org/0000-0002-9859-872X; Email: amandam.correia@yahoo.com.br ORCID iD: http://orcid.org/0000-0003-1326-6863; Email: laisml13@hotmail.com ORCID iD: http://orcid.org/0000-0001-8265-9842; Email: saby_santana17@yahoo.com.br ORCID iD: http://orcid.org/0000-0001-8493-3876; Email: alanapriscilla28@yahoo.com.br ORCID iD: http://orcid.org/0000-0003-4591-786X; 3 Nurse, Master of Nursing, Associate Professor of the University Center Anhanguera in Niterói, Rio de Janeiro (RJ), Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Then, in the first half of the 20th century by the process of institutionalization of labor ceases to be a private place and passes to be institutionalized, with the creation of sectors such as the maternity, creating an event controlled, and the household ends up being extinguished. 2 In this sense, the creation of specific hospitals for the vaginal labor (maternities) aimed to create both a space of teaching and practice of medicine as a place where women feel safe to give birth. The change of home birth, assisted by midwives for the hospital childbirth, conducted by doctors, gave the obstetric care new meanings and paradigms in the care of the woman.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The cause effect relationship in labour pain does not always correspond to a clinical response; what matters is to understand the pain felt by the pregnant woman and to offer pain release. [2] Name & Address of Corresponding Author Dr. Atul Kumar Singh Assistant Professor, Dept. of Anaesthesia, Government Doon Medical College, Dehradun.…”
Section: Introductionmentioning
confidence: 99%